2016
DOI: 10.3390/ijms17030357
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Glutamate Transporters Are Involved in the Development of Electroacupuncture Tolerance

Abstract: Background: Electroacupuncture (EA) tolerance is a gradual decline in EA antinociception because of its repeated or prolonged use. This study aims to explore the role of spinal glutamate transporters (GTs) in EA tolerance (EAT). Methods: Rats were treated with EA once per day for eight consecutive days, and their L4-5 spinal cords were collected at days 0, 2, 4, 6 and 8. The levels of three spinal GTs and their mRNAs were detected with Western blot and pPCR, respectively. Then, riluzole, a positive GT regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Several researches indicated that EA-induced analgesia lasted for 12 h [ 41 ] while EA-induced mRNA expression began in 0–3 h and reached a peak level during 2–24 h in rats [ 42 , 43 , 44 ]. It is proteins (peptides), rather than their genes, that have direct effect on EAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches indicated that EA-induced analgesia lasted for 12 h [ 41 ] while EA-induced mRNA expression began in 0–3 h and reached a peak level during 2–24 h in rats [ 42 , 43 , 44 ]. It is proteins (peptides), rather than their genes, that have direct effect on EAA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that glutamate transporters are also involved in EA analgesia. Cui et al [ 42 ] demonstrated that spinal glutamate transporters (GLAST, GLT-1 and EAAC1) were up-regulated by EA in healthy rats with nociceptive threshold increased. Further, pharmacological studies showed that CFA- [ 77 ] and spared nerve injury-induced [ 78 ] decline in spinal GLAST and GLT-1 could be reversed by EA stimulation, showing they contributed to EA-induced antinociceptive effect in rats.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very little neuroscience research has explored the effects of acupuncture on the role of glutamate in neuropsychiatric disorders. While studies of acupuncture analgesia indicate that acupuncture stimulation may modulate levels of expression of glutamate expression and its receptor, as well as EAAT expression (79, 80), no existing studies have reported on acupuncture-induced modulation of the glycine transporter or other upstream regulatory mechanisms (e.g., D-amino acid oxidase and the amino acid transporter system).…”
Section: Acupuncture Modulates Glutamate Neurotransmissionmentioning
confidence: 99%
“…Repeated EA is more commonly used than continuous EA for pain therapy in clinical practice. Cui et al (2016, 2017a) stimulated rats with 2/15 Hz and 2 Hz EA (30 min/day, total 8 days), and found that the pain thresholds decreased from 59.6 ± 4.6% and 61.4 ± 5.5% at day 1–2.1 ± 4.1% and 1.9 ± 7.4% at day 8, respectively, showing that repeated EA can elicit chronic EAT. Wang et al (2002) used 2 Hz EA for 30 min every time for total 6 times with different intervals (0, 1, 2, and 3 days, respectively) in rats, and found that EA with the interval of 1 day induced EAT whereas EA with the interval of 3 days produced potent analgesia, showing that EA interval is an important factor influencing the development of EAT.…”
Section: Discussionmentioning
confidence: 99%